Developing an automated system for shoe sole halogenation - Sepúlveda, João (1997)
This paper describes a project developed in the Department of Industrial Electronics for a shoe wear manufacturer. It envisaged the study and automation of a human operated position of a shoe production line. A trade of investment and operational costs, technical feasibility and environmental benefits pointed to the selection of the shoe’s sole halogenation position. This operation, manually performed, is done before glue application. Its purpose is the preparation of the shoe sole to receive, in good conditions, the glue. The chemical material used is toxic and harmful to operators. The developed system integrates a manipulator and an artificial vision system. The results that emerged from the experimental tests demonstrated that the proposed automated system works as desired. The system exhibits the additional advantage of performing the halogenation procedure in almost half of the time required by a human operator. The image processing algorithms included in the system software are fast enough to enable image acquisition and processing as well as the transmission of the path to the robot controller, on line.